INTEGRASI NILAI KARAKTER CINTA TANAH AIR DALAM PEMBELAJARAN PAK DI MASA PANDEMI COVID 19 - Martha Lambiombir; Liza Souisa; William Labobar (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2021)
This study aims to analyze the integration of the character values of love for the homeland in PAK learning during the covid 19 pandemic at Murnaten Christian Middle School, Kec. Taniwel Kab. Seram bagian Barat. Using qualitative research methods, through interviews and documentation. The results of the study include (1) Students' views on Character Education that Takes place in Schools shows that the learning that takes place in the classroom by PAK teachers has conveyed about forms of character education, and is related to the character of love for the homeland they already know which is emphasized. about using time at home by studying diligently, repeating the lessons taught by the teacher when at school, (2) An overview of the reality of teenagers with their respective characters and the attitude of love for the country through diligent study in the Covid 19 pandemic period that is diligent in studying What happens to students is not completely like that, they feel that their learning time is only when they want to do homework (PR). However, there are still students who manage their study time during the day and at night. PAK teachers during this pandemic assess that students are no longer studying well, students play more, (3) Strategies for Strengthening Character Education of Students in Forming Attitudes of Love for the Motherland through Diligent Learning activities such as face-to-face learning in class for some time, confirming or building children's character education continues to be carried out.Keywords: Character Values, Love for the Homeland, PAK Learning